A UAV Case Study with Set‐based Design. Issue 1 (16th August 2018) - Small, Colin; Buchanan, Randy; Pohl, Edward; Parnell, Gregory S.; Cilli, Matthew; Goerger, Simon; Wade, Zephan
Abstract: The DoD and Engineered Resilient Systems (ERS) community seek to leverage the capabilities of model‐based engineering (MBE) early in the design process to improve decision making in AoAs. Traditional tradespace exploration with point‐based design often converges quickly on a solution and engineering changes are required after this selection. Set‐based design considers sets of all possible solutions and enables down‐selecting possibilities to converge at a final solution. Using an Army case study and an open source excel add‐in called SIPMath, this research develops an integrated MBE model and example that simultaneously generates numerous designs through physics models into the value and cost tradespace allowing exploration for set‐based design analysis and producing a better efficient frontier than traditional point‐based design AoAs. Grouping design decisions into sets based on their characteristic decision, and simultaneously evaluating the value and cost tradespace, allows for a set‐based design approach that provides insight into the design decisions.